Omar ibn Faraj al-Rakhji: His Biography and His Political and Administrative Role in the Abbasid State - Ibrahim Mohammed , Assist. Prof. Dr. Moayad (Basra studies journal, 2026)
ʿUmar ibn Faraj al-Rakhjī is regarded as one of the prominent political and administrative figures in Abbasid history, owing to the sensitive responsibilities he undertook, which had a direct impact on supporting the authority of the Abbasid caliphs and strengthening their influence within the institutions of the state. Al-Rakhjī rose to prominence during a period marked by political instability and intense conflicts within the caliphal establishment, a context that enabled him to gain the trust of several caliphs who entrusted him with complex and demanding tasks. As the scope of his powers expanded, his administrative influence accumulated, allowing al-Rakhjī to occupy an advanced position within the Abbasid administrative hierarchy and to become one of the effective instruments of authority in consolidating the prestige of the state. However, political shifts and changing balances of power led to the decline of his standing. He was dismissed from his posts, stripped of his privileges, and his wealth and palaces were confiscated by order of the Abbasid caliph al-Mutawakkil (232–247 AH / 847–861 CE). His career ultimately ended in imprisonment, where he met his death as a result of the harsh treatment and physical and psychological oppression he endured—an episode that vividly reflects the nature of political struggles and the volatility of power in the Abbasid era.